Effectiveness of Boycott Behavior and Consumer Knowledge on Brand Switching (Case Study of UBSI Students) - Nuraeni, Yuni Siti; Aprita, Yessica Mega; Haryati, Tri (Valid: Jurnal Ilmiah, 2025)
The decision to switch brands in a phenomenon such as the war in Gaza, particularly in Indonesia, can be influenced by a variety of factors, including boycotting Israeli-affiliated products, and consumer knowledge of a product, which becomes the foundation of consumer behavior and thus a driving factor in brand switching decisions. As a result, more research is needed to determine how boycott behavior and consumer understanding affect brand switching. The research was carried out at UBSI Kramat 98 Campus, with 4th semester management study program students from the even years 2024/2025 serving as the research sample. Purposive sampling was employed to recruit 126 participants. This study takes a quantitative approach, utilizing SPSS multiple regression analysis techniques. The findings of this study show that boycott behavior and consumer knowledge have a significant effect on brand switching at the same time, and that boycott behavior has no significant effect on brand switching while consumer knowledge does.